ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS WHO HAVE HAD COVID-19 - Abdurakhmanov, F.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2026)
From the very first report of mass mortality among diabetic patients infected with COVID-19 infection, emphasis was placed on the severity of damage to the respiratory system in the form of acute respiratory distress syndrome in adults. The unifying factor in the pathogenesis of such a fatal change was the development of dysfunction of the endothelial system (DES), which leads not only to systemic inflammatory damage to the vascular endothelium but also to its consequences in the form of increased blood clotting and a decrease in fibrinolysis processes. The changes that occur in the body of patients after COVID-19 do not disappear completely. First of all, this should be noted about patients with chronic morbid backgrounds, such as, for example, type 2 diabetes mellitus (T2DM). In our study, endothelial function conditions were evaluated in 92 patients who have T2DM. Three cohorts of patients were organized. Indicators characterizing the state of DES were examined in blood obtained by puncture from a peripheral vein.